2019
DOI: 10.1021/acs.analchem.9b01447
|View full text |Cite
|
Sign up to set email alerts
|

Surface Glycoproteomic Analysis Reveals That Both Unique and Differential Expression of Surface Glycoproteins Determine the Cell Type

Abstract: Proteins on the cell surface are frequently glycosylated, and they are essential for cells. Surface glycoproteins regulate nearly every extracellular event, but compared with global analysis of proteins, comprehensive and site-specific analysis of surface glycoproteins is much more challenging and dramatically understudied. Here, combining metabolic labeling, click-chemistry and enzymatic reactions, and mass spectrometry-based proteomics, we globally characterized surface glycoproteins from eight popular types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 71 publications
(120 reference statements)
0
20
0
Order By: Relevance
“…Analyzing glycoproteomes from whole-cell lysate generates confounding artifacts that complicate determination of what glycoforms are biologically relevant and present on the cell surface. Several approaches have been developed to label cell-surface glycoproteins on live cells, prior to cell lysis and protein extraction ( 306 , 307 ). One variation functions similarly to the approaches above: sialic acids are oxidized on live cells via mild periodate treatment, and aldehyde-containing sialylated glycopeptides are captured on hydrazide beads.…”
Section: Chemical Coupling Strategiesmentioning
confidence: 99%
“…Analyzing glycoproteomes from whole-cell lysate generates confounding artifacts that complicate determination of what glycoforms are biologically relevant and present on the cell surface. Several approaches have been developed to label cell-surface glycoproteins on live cells, prior to cell lysis and protein extraction ( 306 , 307 ). One variation functions similarly to the approaches above: sialic acids are oxidized on live cells via mild periodate treatment, and aldehyde-containing sialylated glycopeptides are captured on hydrazide beads.…”
Section: Chemical Coupling Strategiesmentioning
confidence: 99%
“…Witzke and co-workers [76] compared two labeling compounds, DBCO-sulfo-biotin and DBCO-PEG4desthiobiotin, and found that 356 proteins were quantified using the biotin probe and 463 using the desthiobiotin probe. Wu and coworkers [77,78] combined azido-based metabolic labeling and copper-free click chemistry with MS-based proteomics to selectively enrich cell surface glycoproteins and reveal the differential expression of surface glycoproteins of different cell types. Recently, they combined a boosting approach that incorporated TMT with Ac4GalNAz labeling and copper-free chemistry to label secreted glycoproteins from cultured cells without serum starvation [79].…”
Section: Metabolic Labeling Of Glycoproteinsmentioning
confidence: 99%
“…2,9 The majority of cell surface proteins are glycosylated, and the most common ones are protein N-and Oglycosylation. [10][11][12][13][14] Aberrant glycosylation can alter proteinprotein interactions, which has been correlated with disease initiation and development. 15,16 For instance, changes in the glycosylation of CD44, a cell surface receptor involved in cancer proliferation and migration, can signicantly affect its binding towards the ligand of hyaluronic acid and thus change cancer cell signaling.…”
Section: Introductionmentioning
confidence: 99%